Redescription of a poorly known upogebiid mud shrimp Gebiacantha acanthochela (Sakai, 1967) and description of a new species of the genus from the Ryukyu Islands, Japan (Decapoda: Gebiidea) - Komai, Tomoyuki (Zootaxa, 2020)
Two species of the upogebiida mud shrimp genus Gebiacantha Ngoc-Ho, 1989, currently represented by 19 described species, are reported from the Ryukyu Islands, Japan. The first, G. acanthochela (Sakai, 1967), is redescribed in detail based on two female specimens from Amami Islands the second discovered since the original description, enabling better assessment of its diagnostic characters. The second, G. fortispinata n. sp., is described on the basis of a single female holotype from Okinawa Island. It appears closest to G. multispinosa Ngoc-Ho, 1994, known with certainty only from New Caledonia, but the proportionally narrower telson with a more deeply notched posterior margin and the distally unarmed pereopod 3 merus distinguish the new species from G. multispinosa. Three species of Gebiacantha, including G. sagamiensis Komai, 2017, are now known from Japanese waters.